2019
DOI: 10.1002/ejic.201900120
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Thermal Properties of Cs2SnI6xBrx Mixed Perovskite Solid Solutions

Abstract: Cs 2 SnI 6-x Br x (x = 0-6) solid solutions have been synthesized by chemical solid solution reaction in conjunction with sintering under vacuum. The Rietveld refinements of powder Xray diffraction (XRD) patterns indicate that all the samples are cubic, with a symmetry of Fm3m. The lattice parameter a decreases linearly as a function of the Br content in Cs 2 SnI 6-x Br x . Raman spectra suggest that the new Raman peaks might derive from the short-range ordering of I/Br anions. The UV/Vis reflec- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…The emission spectra of the Cs 2 SnX 6 NCs (X = Cl, Br, Br 0.5 I 0.5 , I), reported in Figures 3A,B, are peaked at 444 nm (2.80 eV), 603 nm (2.06 eV), 663 nm (1.87 eV), and 790 nm (1.57 eV), by changing the halide content from Cl to I, with corresponding full-width at half maximum (FWHM) of 117, 122, 165, and 112 nm, respectively. The values we found for Cs 2 Sn(Br 0.5 I 0.5 ) 6 and Cs 2 SnI 6 NCs are considerably higher than the fundamental gap energies reported for these compounds in the bulk form (1.43 and 1.3 eV, respectively), thus suggesting a significant blue-shift in the NC optical properties due to quantum confinement effects (Kaltzoglou et al, 2015(Kaltzoglou et al, , 2016Yuan et al, 2019). The values of the band gap extracted from the Tauc plot of the absorbance spectra are reported in Table S1 of the Supplementary Material and confirms the scaling of the emission with a possible dependence of the Stoke shift with the halide nature.…”
Section: Resultscontrasting
confidence: 66%
“…The emission spectra of the Cs 2 SnX 6 NCs (X = Cl, Br, Br 0.5 I 0.5 , I), reported in Figures 3A,B, are peaked at 444 nm (2.80 eV), 603 nm (2.06 eV), 663 nm (1.87 eV), and 790 nm (1.57 eV), by changing the halide content from Cl to I, with corresponding full-width at half maximum (FWHM) of 117, 122, 165, and 112 nm, respectively. The values we found for Cs 2 Sn(Br 0.5 I 0.5 ) 6 and Cs 2 SnI 6 NCs are considerably higher than the fundamental gap energies reported for these compounds in the bulk form (1.43 and 1.3 eV, respectively), thus suggesting a significant blue-shift in the NC optical properties due to quantum confinement effects (Kaltzoglou et al, 2015(Kaltzoglou et al, , 2016Yuan et al, 2019). The values of the band gap extracted from the Tauc plot of the absorbance spectra are reported in Table S1 of the Supplementary Material and confirms the scaling of the emission with a possible dependence of the Stoke shift with the halide nature.…”
Section: Resultscontrasting
confidence: 66%
“…For 3D NCs synthesized with OLA, Cs 2 SnI 6 and Cs 2 SnBr 6 are found to have gaps of 1.57 and 3.33 eV, that are higher than those of their relative bulk forms (1.3 and 2.7 eV, respectively). (Kaltzoglou et al, 2016;Yuan et al, 2019). Moving to 2D structures, on the other hand, we can observe that the gap energy becomes even higher, increasing linearly with increasing the amine length (Figure 4).…”
Section: Absorptionmentioning
confidence: 88%
“…These results are in line with the data reported in literature and coherent with a decrease of the ionic radius moving from iodine to bromine. (Kaltzoglou et al, 2016;Saparov et al, 2016;Yuan et al, 2019).…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…As for Cs 2 Sn(I x Br 1− x ) 6 , the bandgap was increasing from about 1.3 to 3.0 eV while decreasing the x value from 1 to 0. [ 42,43 ] Taking x = 0.5 as example, that is Cs 2 Sn(I 0.5 Br 0.5 ) 6 the PL peak was located at 826 nm. The data of the present study showed that the PL peak of CsSnI 0.5 Br 0.5 was located at 770 nm.…”
Section: Resultsmentioning
confidence: 99%